Sistem Informasi Kenaikan Gaji Berkala Pns Pemerintah Provinsi Kepulauan Riau - Hendranita Sitorus; Mochammad Rizki Romdoni (Jurnal Bangkit Indonesia, 2019)
Periodic Salary Increases is a kind of salary increases given to civil servants once in two years who is qualified according to the law. Making a Periodic Salary Increases Letter in Provincial Government of Riau Island. is still in manual process by typing the letter one by one and saved in Staffing Administrator's computer. This might cause an incorrect in Periodic Salary Increases Decree. Moreover, any trouble in the administrator's computer could also cause files lost and make Periodic Salary Increases Decree arrived late at BPKAD of Province of Riau Island.. From cases above, we need a Periodic Salary Increases Information System based on website to support Staffing create Periodic Salary Increases Decree.Author design a modeling system using structured method: Context Diagram, DFD, and ERD (Entity Relationship Diagram). This research produce Periodic Salary Increases Information System to process Periodic Salary Increases Decree, requirements, and to produce Periodic Salary Increases Decree until it suitable to send to BPKAD of Province of Riau Island.